Psychometric properties of the Indonesian version of the Quality of Life Index (QLI-I) among family caregivers of dependent older persons with type 2 diabetes mellitus - Siregar, Rinco; Kritpracha, Charuwan; Chinnawong, Tippamas; Latour, Jos M. (Belitung Nursing Journal, 2025)
Background: The quality of life (QoL) of family caregivers supporting older persons with functional dependence due to Type 2 Diabetes Mellitus (T2DM) is a growing concern. Accurately assessing caregiver well-being requires culturally appropriate, valid, and reliable instruments. However, such tools remain limited in the Indonesian context. Objective: This study aimed to translate the Quality of Life Index (QLI) into Indonesian and evaluate the psychometric properties of the Indonesian version (QLI-I) among family caregivers of dependent older persons with T2DM. Methods: Brislin’s back-translation method was used to ensure linguistic and conceptual equivalence in the translation process. Content validity was assessed by a panel of five experts. Psychometric evaluation was conducted on a purposive sample of 394 family caregivers recruited from eleven community health centers in Medan, Indonesia. Construct validity was examined using confirmatory factor analysis (CFA), while convergent validity and construct reliability (CR) were analyzed to assess measurement accuracy. Results: The Indonesian version of the Quality of Life Index (QLI-I) demonstrated strong construct validity, with standardized factor loadings ranging from 0.707 to 0.870. CFA indicated an acceptable model fit based on the following indices: Root Mean Square Error of Approximation (RMSEA) = 0.067, ratio of chi-square to degrees of freedom (CMIN/df) = 2.779, Comparative Fit Index (CFI) = 0.906, Incremental Fit Index (IFI) = 0.906, Goodness of Fit Index (GFI) = 0.814, and Tucker-Lewis Index (TLI) = 0.898. Composite Reliability (CR) values were high across all domains: Health/Functioning (HF) = 0.957, Family (FA) = 0.876, Social/Economic (SE) = 0.924, and Psychological/Spiritual (PS) = 0.922. Average Variance Extracted (AVE) values met the recommended threshold for each domain: HF = 0.633, FA = 0.586, SE = 0.605, and PS = 0.627. All constructs demonstrated acceptable discriminant validity, confirming the distinctiveness of each domain. Conclusion: The QLI-I is a valid and reliable instrument for assessing the QoL of family caregivers of dependent older persons with T2DM. Its use in clinical and community settings can support nurses and healthcare professionals in identifying caregiver needs and developing culturally appropriate, evidence-based interventions to enhance caregiver well-being.